Complimentary Feeding Substitutions of Pumpkin and Snakehead Fish Flour - Imelda Telisa; Ajeng Santika Putri; Terati Terati; Yuli Hartati; Arif Dwisetyo Haripamilu (Jurnal Gizi Prima (Prime Nutrition Journal), 2022)
Background. Malnutrition, notably underweight in infants, is a severe nutritional problem that must be addressed. To solve the problem of being skinny in toddlers by utilizing local food, complementary feeding with high protein and vitamin A levels must be offered. Pumpkin is abundant in beta-carotene, while snakehead fish is one of the animal protein sources with a high protein level. Baby porridge using snakehead fish meal and pumpkin flour as a substitute is predicted to be a complementary feeding that provides high protein and vitamin A. The goal of this study was to determine the acceptability of complementary feeding porridge and the effect of the substitution of pumpkin flour and snakehead fish on the level of nutrients and beta-carotene.Research Methods. This was a randomized controlled trial with two components and three degrees of substitution treatment of pumpkin flour and snakehead fish meal in the ratios of 100g:50g, 75g:75g, and 100g:50g. Proximate and beta-carotene analyses are used to determine nutritional level. The Friedman test was used to do a statistical analysis of the preference/hedonic test.Research Result. There are differences between complementary feeding made from pumpkin flour and snakehead fish and instant complementary feeding in terms of carbohydrate, protein, fat, energy, water level, ash level, and beta-carotene levels. The color and flavor of the complementary feeding are affected by the percentages of snakehead fish meal and pumpkin flour. Conclusion. Formula 1, with a ratio of 100g:50g, is the most popular formula for pumpkin flour and snakehead fish meal.